2011
DOI: 10.1101/cshperspect.a006726
|View full text |Cite
|
Sign up to set email alerts
|

mGluR1/TRPC3-mediated Synaptic Transmission and Calcium Signaling in Mammalian Central Neurons

Abstract: Metabotropic glutamate receptors type 1 (mGluR1s) are required for a normal function of the mammalian brain. They are particularly important for synaptic signaling and plasticity in the cerebellum. Unlike ionotropic glutamate receptors that mediate rapid synaptic transmission, mGluR1s produce in cerebellar Purkinje cells a complex postsynaptic response consisting of two distinct signal components, namely a local dendritic calcium signal and a slow excitatory postsynaptic potential. The basic mechanisms underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 122 publications
(171 reference statements)
4
61
0
Order By: Relevance
“…Similar to the mGluR1-mediated calcium transients, SCA2 PNs exhibited significantly larger EPSCs as compared to WT PNs across stimulus strengths (Figure 4B). Notably, larger EPSCs are not simply a consequence of increased calcium mobilization as intracellular calcium increases are not required for activation of the TRPC3 channel (Dzubay and Otis, 2002; Hartmann et al, 2008, Hartmann et al, 2011Hartmann et al, 2011Hartmann et al, 2011). Thus, these results suggest a comprehensive increase in mGluR1-mediated signaling, possibly due to some positive feedback occurring early in the signal transduction cascade.
10.7554/eLife.26377.005Figure 4.Synaptic mGluR1 EPSCs are significantly larger in SCA2 PNs.( A and B ) Slow mGluR1 EPSCs in response to 5 and 10 pulse, 100 Hz stimuli applied to PFs.
…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the mGluR1-mediated calcium transients, SCA2 PNs exhibited significantly larger EPSCs as compared to WT PNs across stimulus strengths (Figure 4B). Notably, larger EPSCs are not simply a consequence of increased calcium mobilization as intracellular calcium increases are not required for activation of the TRPC3 channel (Dzubay and Otis, 2002; Hartmann et al, 2008, Hartmann et al, 2011Hartmann et al, 2011Hartmann et al, 2011). Thus, these results suggest a comprehensive increase in mGluR1-mediated signaling, possibly due to some positive feedback occurring early in the signal transduction cascade.
10.7554/eLife.26377.005Figure 4.Synaptic mGluR1 EPSCs are significantly larger in SCA2 PNs.( A and B ) Slow mGluR1 EPSCs in response to 5 and 10 pulse, 100 Hz stimuli applied to PFs.
…”
Section: Resultsmentioning
confidence: 99%
“…For TRPC3 in cerebellar Purkinje cells, a PLC-independent gating mechanism relies on the small GTP-binding protein Rho and subsequent phospholipase D activation (Glitsch, 2010). TRPC channels are known to be redundantly activated and appear to be located at a point of intersection of diverse signaling pathways (reviewed in (Hartmann et al, 2011)). Moreover, TRPC channels in neurons are part of multi-protein postsynaptic signaling complexes that also contain neurotransmitter receptors, including the NMDAR (reviewed in (Ambudkar et al, 2006)).…”
Section: Discussionmentioning
confidence: 99%
“…; Hartmann et al . ), were disrupted in PCs of SCA1 mice. Furthermore, fast confocal Ca 2+ imaging revealed that PCs in SCA1 mice exhibit reduced mGluR1‐mediated dendritic Ca 2+ signals, which were not detected in a previous widefield fluorescence imaging study (Inoue et al .…”
Section: Introductionmentioning
confidence: 95%